Fraction Card Media and Mathematics Learning Outcomes: An Experimental Study among Elementary School Students - Penu, Marice Jublina; Hendrik, Hingrida Margarita Anastasia; Mbuik, Heryon Bernard (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of fraction card media on mathematics learning outcomes in fraction material for fifth-grade students at SDN Tunfeu 1 Nekamese. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The population and sample consisted of 28 fifth-grade students selected using saturated sampling techniques. Data collection techniques included tests, observation, and documentation. Data analysis used descriptive statistics, normality tests, paired sample t-tests, and N-Gain tests. The findings showed that the average pretest score of 54.46 increased to 86.61 in the posttest. The hypothesis test indicated a significance value of 0.000 (<0.05) and t-count value of 16.493 > t-table 1.701, indicating that there was a significant effect of fraction card media on students’ mathematics learning outcomes. The N-Gain value of 0.712 was categorized as high. The study concludes that fraction card media effectively improves mathematics learning outcomes in fraction material among elementary school students. The use of concrete and interactive learning media helps students understand abstract mathematical concepts more meaningfully and actively.